Molecular Study of Regulatory Gene (Ler) in Enteropathogenic Escherichia Coli (EPEC) of Diarrheagenic Patients - AL-Imam, Mokhtar Jawad Kadhim; Flayyih, May Talib (Iraqi Journal of Science, 2020)
The locus of enterocyte effacement LEE-encoded regulator (Ler( is a global regulator of multiple virulence genes expression in the Enteropathogenic Escherichia coli (EPEC), including those encoding the type III secretion pathway and adhesion proteins such as intimin. Ler is central to the process of the formation of the attaching and effacing (AE) lesions. This study aimed to perform the molecular detection of Ler gene in EPEC, since there is no related previous study in Iraq. Two hundred and fifty stool specimens from children under two years of age for both sexes were collected from some Iraqi hospitals. All isolates were diagnosed according to morphological characteristics and biochemical tests. The results showed that 140 (56%) samples were identified as E.coli, while 8 (5.7%) isolates were identified as EPEC as confirmed by using VITEK 2 system. Susceptibility test was determined for all EPEC isolates to 16 different antibiotics. The results showed that 100%of these isolates were resistant to Ampicillin, Cefazolin, Ceftriaxone, Cefepime, Trimethoprim and Ceftazidime, whereas resistance values to Nitrofurantoin, Cefoxitin and Gentamicin were 66%, 40%, and 15% respectively. However 100% of the isolates were sensitive to Piperacillin, Ertapenem, Imipenem, Amikacin, Ciprofloxacin, Levofloxacin and Tigecycline. Monoplex pattern of PCR was used for detecting 16SrRNA, eae, stx1, lifA and Ler genes in EPEC. The results showed that the isolates of E.coli were positive for 16SrRNA, eae, lifA and Ler, while no bands of stx1 appeared.